Проблеми та особливості формування доходів домашніх господарств - Вініченко, Ігор Іванович; Vinichenko, Igor; Шутько, Тетяна Ігорівна; Shutko, Tatiana; Чорнобай, Артур Володимирович; Chornobai, Artur (Інститут підготовки кадрів державної служби зайнятості України, ТОВ `Редакція журналу `Економіка та держава`, 2021)
У статті здійснено аналіз складу, динаміки та резервів збільшення доходів домашніх господарств в Україні. Установлено, що домашні господарства є суб'єктами економічної діяльності, які пов'язані із веденням домашнього господарства та переважно зі споживанням. Визначено, що поняття "домашні господарства" охоплює економічні процеси та об'єкти, котрі відбуваються у місцях постійного проживання населення. Встановлено, що прибутки домогосподарств суттєво впливають на матеріальне становище українських родин та мають вагоме значне в економічній системі країни. Установлено, що резерви зростання прибутків домашніх господарств повинні оптимізуватися за трьома напрямами: громадяни, підприємство та держава. Запропоновано заходи сприяння підвищенню зростання офіційних прибутків домашніх господарств та зміцненню економічної системи країни. This article examines the economic analysis of the composition, dynamics and reserves of increasing household incomes in Ukraine. The significant contribution of scientists to the development of theoretical and methodological aspects of the problems of household income policy has been studied. It was found that with the fall of gross domestic product, household consumption of services and goods may decrease to some extent. It has been established that households are subjects of economic activity that are related to running a household, ie mainly to consumption. It is defined that the concepts of households cover economic processes and objects that occur where people and families live permanently. It is determined that the main sources of formation of monetary resources of households are wages, income from entrepreneurship and self-employment, sales of agricultural products, personal and household property, real estate, assistance, benefits, subsidies, pensions, scholarships and other financial and non-financial income. It was found that household incomes significantly affect the financial situation of Ukrainian families, as well as occupy a significant place in the economic system. It is established that the reserves of household income growth should be optimized in three areas: the citizen, the enterprise and the state. It was found that in order to attract and retain competent workers, form their loyalty to the company and increase motivation, in addition to basic wages, bonuses, surcharges and allowances, the employer must offer other benefits and incentives of an economic nature that are not directly related to employment and responsibilities. It has been established that households, operating in an unstable market environment, should take a prudent approach to economic decisions in order to neutralize the negative factors of influence and provide a sufficient level of income to ensure a decent standard of living for their members. It is established that the lack of appropriate state mechanisms for the transformation of household savings into investment potential creates significant risks of loss of income from potentially capable domestic economic resources generated by households. It has been found that household incomes are the best tool for measuring the well-being of the population. Measures that should lead to an increase in official household incomes and strengthen the economic system of our country as a whole have been studied.
Problems and features of household income formation
Keywords: домашнє господарство; household; прибуток; income; праця; labor; трудовий дохід; labor income; держава; state